Percursos juvenis e trajetórias escolares : vidas que se tecem nas periferias das cidades - Silva, Carla Regina (2011)
In Brazil, the youth, besides the historic numerical relevance in the drawing of population, has become an important social category, that brings specific demands, wherein education and work are central themes. Recently, we are watching the settlement of an institutional framework, specific for youth, but, in what is intended in terms of social rights, has not yet become effective. Thus, the most part of the Brazilian youth, in other words, the poor youth or from popular groups, is the group that presents the highest vulnerability, represented by a major quantitative and qualitative educational gap and lack of integration with real world (related to jobs). This study has addressed this issue in order to correlate and understand the macrossocial interactions in what could be called microssocial - life path and school career of four poor young students, who live in suburbs of a medium-sized city in the countryside of São Paulo state. Research has made use of methodological procedures based on a combination of strategies, including, monitoring either, individual and collectives in the territory - articulation of resources in social field, dynamization of the attention network and workshops of activities, projects and dynamics and, speccialy, apprehension of research territory. Those strategies were formulated on the basis of social occupational therapy and education in a Freire perspective, also supported by the participant objectification proposed by Pierre Bourdieu. The socio-historical approach, chosen in this work, supported the research and contributed to analysis the relations among the public policies aimed at youth, mainly, the educational policies and how them are reflected in the paths of life of those youngsters. Consequently, as we have policies according capitalist system of production and contemporary neo-liberal doctrine, we got little efficiency strategies, such as expanding access to secondary and superior degrees, the expansion of superior degree and its alternative forms the inclusion of vulnerable groups, that resulted vulnerable, because their inability to meet the demands of individuals of the poor youth. In the same way, the family, society and others institutions also came to be insufficient or inadequate to supports the leverage the life‟s projects presented by the individuals of the research. These youngsters, though, immersed in difficulties, limitations, and precariousness, projected possibilities, until now, show that failures shoot down upon specific paths, highlighting the need for a broader network of protection and support, capable of transforming life, where in education has a fundamental role.